Correlation between Microleakage and Absolute Marginal Discrepancy in Zirconia Crowns Cemented with Four Resin Luting Cements: An In Vitro Study - Abad-Coronel Cristian; Li Jeanette; Martínez-Rus Francisco; Pradíes Guillermo (Hindawi Limited, 2016)
Objectives. To evaluate microleakage and absolute marginal discrepancy (AMD) and to assess correlation between AMD and microleakage with four resin luting cements. Material and Methods. 20 extracted human third molars were prepared for full-coverage crowns. 20 zirconia copings were made (LAVA, 3M ESPE) and cemented. Specimens were randomly allocated for each used type of cement into 4 groups, RelyX® (Rx), Multilink® (Mk), PANAVIA 2.1® (P), and Maxcem® (Mx) and immersed in 10% safranin for 72 hours. 20x magnification lenses were used to observe microleakage areas (μm2) and images software was used to measure AMD areas (μm). Discrepancy and microleakage between the cements were compared with one-way ANOVA test with confidence interval of 95%. Results. Rx Group showed microleakage has lowest value and AMD has highest value. P Group showed microleakage has the highest value and Mk Group presented AMD has lowest value. There were no significative differences between the cements. There were no linear correlations between microleakage and AMD; however a complex regression statistical model obtained allowed formulating an association between both variables (microleakage = AMD0,896). Conclusions. No significative differences were found among 4 types of cements. No linear correlations between AMD and microleakage were found. Clinical Significance. AMD is not easily related to microleakage. Characteristics of cements are fundamental to decreasing of microleakage values.